Gender differences in the dimensions of tricuspid valve orifice and leaflets in the Bangladeshi population - a morphometric study (Bangladesh Journal of Medical Science, 2021)
Background: The present study aims to measure the circumference, length, and breadth of thedifferent leaflets of the tricuspid valve orifice in men and women to enable improved treatmentand management for cardiac patients in future.Materials and methods: In this cross-sectionalstudy, samples of the cadaveric heart (41 male, 19 female, and age ranging between 20 and70 years) were collected within 12–24 hours of death from unclaimed dead bodies that wereautopsied in the morgues of Sir Salimullah Medical College (SSMC) and Dhaka Medical College(DMC), Dhaka, Bangladesh. Unpaired t-test was conducted to determine significant genderdifferences using SPSS 16.Results: There were no significant difference in the circumference,length, and breadth of the anterior, posterior, and septal leaflets of tricuspid valves between menand women.Conclusion :The circumference, length, and breadth of the anterior, posterior,and septal leaflets of tricuspid valves are similar between men and women in the Bangladeshipopulation. Therefore, there will be no specific difference in the surgical and therapeutictreatment for men and women.Bangladesh Journal of Medical Science Vol.20(2) 2021 p.342-347